2023
DOI: 10.3390/brainsci13060936
|View full text |Cite
|
Sign up to set email alerts
|

Association of Motoric Cognitive Risk Syndrome with Sarcopenia and Systemic Inflammation in Pre-Frail Older Adults

Abstract: Motoric cognitive risk syndrome (MCR) is defined by the presence of slow gait and subjective cognitive decline. It is well recognized as a prodrome for dementia, but the biological mechanism and trajectory for MCR are still lacking. The objective of this study was to explore the association of MCR with body composition, including sarcopenia and systemic inflammation, in pre-frail older adults in a cross-sectional study of 397 pre-frail community-dwelling older adults. Data on demographics, physical function, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“… 37 , 38 , 39 , 40 Additionally, inflammatory markers were reported to be associated with the two components of MCR: slow gait speed 41 , 42 , 43 , 44 and cognitive complaints. 45 Therefore, we speculate that the potential mechanism by which social frailty influences MCR may be partially attributed to inflammation.…”
Section: Discussionmentioning
confidence: 91%
“… 37 , 38 , 39 , 40 Additionally, inflammatory markers were reported to be associated with the two components of MCR: slow gait speed 41 , 42 , 43 , 44 and cognitive complaints. 45 Therefore, we speculate that the potential mechanism by which social frailty influences MCR may be partially attributed to inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, there is an association between muscle loss and systemic inflammation. Inflammation may play a role in the development of tumors and is related to systemic complications associated with malignancies, further influencing patient prognosis [ 39 , 40 ]. Finally, muscle loss is often associated with malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α/IL-10 ratio serves as a surrogate for immune homeostasis which measures ratio of pro- and anti-inflammatory cytokines. Prior studies have shown that high TNF-α/IL-10 ratio have been associated with frailty, motoric cognitive risk syndrome, severity of burn injury and susceptibility to infections in burn patients ( 25 , 49 ). TNF-α and IL-6 did not significantly differ between groups, possibly due to enrolled participants being pre-frail ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a potent anti-inflammatory cytokine and increases in response to inflammatory cascade ( 23 ). Besides its role in neurodegenerative diseases, low or absent IL-10 in mice has shown to be associated with frailty ( 24 , 25 ).…”
Section: Introductionmentioning
confidence: 99%